The Effect of Online Cart Composition on Cart Abandonment - Hadar, Liat; Steinhart, Yael; Appel, Gil; Shani, Yaniv (Journal of Consumer Research, 2026)
Abstract Online shopping cart abandonment is widespread, causing major losses in potential revenues for e-commerce companies. We expand efforts to mitigate cart abandonment by investigating how the cart’s product composition affects abandonment and testing easy-to-implement interventions. We hypothesize that consumers are more likely to abandon carts containing a higher proportion of hedonic relative to utilitarian products. This cart composition effect arises because carts containing higher hedonic-to-utilitarian product ratios are perceived as more hedonic overall, increasing consumer guilt regarding cart purchase and the likelihood of cart abandonment. Analyses of two large-scale field datasets and four controlled experiments provide converging evidence for the cart composition effect (studies 1A to 3) and the mediating role of perceived hedonism and consumer guilt (studies 2, 4A and 4B). Substantively, we offer empirical support for a practical and easily implemented intervention: using e-commerce recommendation systems to reduce cart abandonment by suggesting utilitarian items (studies 4A and 4B). Our findings suggest that recommendation systems may serve as an effective tool for reducing cart abandonment and underscore the importance of incorporating hedonic value considerations into recommendation algorithms. We conclude by discussing the practical implications of our findings for the development of more effective marketing strategies and improving online conversion rates.